RELEVANCE OF 21ST CENTURY SKILLS IN DEALING WITH SUSTAINABLE DEVELOPMENT GOALS THROUGH THE INDEPENDENT CAMPUS LEARNING PROGRAM - Elly Sukmanasa, Yanti Suryanti, Gusnadi, Gusnadi, Siti Aisyah (Jurnal Pendidikan dan Pengajaran Guru Sekolah Dasar (JPPGuseda), 2023)
Learning in the old curriculum tends to create students who are successful in class, with high GPA and are required to memorize theories and concepts. The impact of this condition is that students have difficulty interacting with the community, because there are no opportunities/opportunities to understand life in society. 21st century learning expects students to have the competence to think critically, creatively, communicatively, and be able to collaborate or 21st century skills. Therefore the opportunity for independent learning can be said as an effort to develop student competence. The research was conducted on 418 students from 4 batches. The instrument in the form of a questionnaire uses a Likert scale. The data obtained were analyzed using descriptive statistics. The results show the relevance of 21st century skills that are able to support the sustainability of sustainable development or SDGs. This finding is evidenced by the average of the four learning skills indicators showing a high value, 3.53. Most of the respondents agreed with the MBKM program and were very satisfied with their learning experience. The relevance of teaching skills through MBKM can be interpreted as an effort to realize the whole human being in facing sustainable development or SDGs. It can be concluded that the MBKM program provides opportunities and opportunities for students to have 21st century skills towards continuing education through the SDGs.